MENGEMBANGKAN (PEMBELAJARAN) BLENDED LEARNING DENGAN SISTEM LINGKUNGAN PEMBELAJARAN VIRTUAL (VLE) DI PTKIN - Rahmat Yusny; Ghufran Ibnu Yasa (Universitas Islam Negeri Ar-Raniry, 2019)
Recently there has been a great interest invested in maximizing higher education students’ knowledge retention as well as increasing students learning experience using web technologies. Many higher education institutions upgrade their learning facilities by integrating virtual learning system to their education provisions. Educational content management system is now a primary requirement in higher education provisions. However, as for the context of Indonesian higher education, upgrading the learning system may mean a total change of the way classes are delivered. Most of Indonesian higher education teachers are those with minimal exposure of virtual technological use in classrooms. Although these teachers are familiar with the common internet tools especially the electronic mail system and internet social media, they are not yet familiar with managing a content management system. Universitas Islam Negeri (UIN) ar-Raniry is one of Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) that share similar context. This study was conducted to explore UIN Ar-Raniry teachers’ readiness in delivering blended learning using Virtual Learning Environment. 124 teachers were participating in this research. The index of technological acceptance is relatively high (3.78). However, on the contrary digital technology use related to delivering lecture is relatively low. The use of e-mail and facebook is relatively popular among these teachers. The study found that teachers are interested in using more convenient digital tools in their classes if the university supports the trainings and assigns educational technology consultant to help them establish the virtual class and help with their technical troubles.